2011
DOI: 10.1371/journal.pone.0026957
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and Cut-Off Values of Pepsinogens I, II and Gastrin 17 for Diagnosis of Gastric Fundic Atrophy: Influence of Gastritis

Abstract: BackgroundTo establish optimal cutoff values for serologic diagnosis of fundic atrophy in a high-risk area for oesophageal squamous cell carcinoma and gastric cancer with high prevalence of Helicobacter pylori (H. pylori) in Northern Iran, we performed an endoscopy-room-based validation study.MethodsWe measured serum pepsinogens I (PGI) and II (PGII), gastrin 17 (G-17), and antibodies against whole H. pylori, or cytotoxin-associated gene A (CagA) antigen among 309 consecutive patients in two major endoscopy cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 45 publications
3
43
1
Order By: Relevance
“…Performance of this test was significantly improved when analysis of H. pylori antibodies has been included [10]. Similar cut-offs, although higher for the pepsinogen I/II ratio ( 5.0), have been identified by an Iranian group for the detection of atrophy [11]. The data also support the role of pepsinogen II being an adequate marker for non-atrophic pangastritis, which is also considered as a risk condition for GC development.…”
Section: Prevention and Screening Of Gastric Cancersupporting
confidence: 52%
“…Performance of this test was significantly improved when analysis of H. pylori antibodies has been included [10]. Similar cut-offs, although higher for the pepsinogen I/II ratio ( 5.0), have been identified by an Iranian group for the detection of atrophy [11]. The data also support the role of pepsinogen II being an adequate marker for non-atrophic pangastritis, which is also considered as a risk condition for GC development.…”
Section: Prevention and Screening Of Gastric Cancersupporting
confidence: 52%
“…In a recent study , designed in our country , the best cutoff value in gastric atrophy assessment was calculated at PGI, 56 ng/ml (sensitivity: 61.9%, specificity: 94.8%) but we used the cutoff value of PGI <88.7 ng/ml (sensitivity and specificity of 64.4% and 43% respectively) for atrophy (Nasrollahzade et al, 2011). That work was an office based study and 309 persons were enrolled but present study was a population based survey on 1390 persons explaining the difference of cutoff between two studies.…”
Section: Discussionmentioning
confidence: 99%
“…Cao et al found a high AUC (0.88) for PgI in patients with GA (Cao et al, 2007). Nasrollahzadeh et al (2011) similarly reported relatively high accuracy (AUC=0.78) for PgI as well as for the combination of PgI and PgI/II ratio (AUC=0.79) for diagnosis GA. Shikata et al (2012) reported a sensitivity and specificity of 71.0% and 69.2% for a combination of PgI and PgI/II ratio to discriminate GC. Miki et al (2003) reported a sensitivity of 80% and a specificity of 70% for the combination of PgI and PgI/II ratio to detect GC.…”
Section: Discussionmentioning
confidence: 93%
“…But, the results of some previous studies showed relatively high accuracy for G17 to differentiate GA or GC. Nasrollahzadeh et al (2011) reported an AUC of 0.77 for G17 to discriminate GA. Kikushi et al (2011) also suggested G17 as good biomarker for diagnosis GA. Regarding the role of G17 pathogenesis of GC (Copps et al, 2009), further studies are warranted to assess the validity of G17 to differentiate GA/GC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation